Morbidly Adherent Placenta: Its Management and Maternal and Perinatal Outcome - Chaudhari, H. K. (J Obstet Gynaecol India, 2016)
OBJECTIVES: The aim of the study was to identify the risk factors predisposing to morbidly adherent placenta and to study the different modes of management and the obstetric and neonatal outcome of these patients. METHODS: This was a retrospective cum prospective observational study conducted in the Department of Obstetrics and Gynaecology in a tertiary care referral hospital in Mumbai from January 2012 to November 2014. RESULTS: The incidence of morbidly adherent placenta was 1.32 per 1000 pregnancies with patient profile comprising second gravida in the age group 26–28 years; 90 % of the patients in this study had previous Caesarean section and co-existing placenta praevia was diagnosed in 63 %. Fifty-three per cent of the women delivered between 35 and 38 weeks and 40 % had elective deliveries. Caesarean section was the mode of delivery in 90 % of the patients. Prophylactic balloon placement in the internal iliac artery followed by classical Caesarean section, uterine artery embolization and post-operative methotrexate was done in 27 % which preserved the uterus and was associated the blood loss of 1000–2000 mL. CONCLUSION: Antenatal diagnosis of morbidly adherent placenta allows for multidisciplinary planning in an attempt to minimize potential maternal or neonatal morbidity and mortality.